Little and Falace's dental management of the medically compromised patient - Kerr, A. Ross; Miller, Craig S.; Rhodus, Nelson L.; Stoopler, Eric T.; Treister, Nathaniel S.; Little, James W., 1934-; Falace, Donald A., 1945-; Little, James W., 1934- (St. Louis, Missouri : Elsevier, 2024)
"Little and Falace's Dental Management of the Medically Compromised Patient, 10th Edition, is thoroughly revised to provide the information needed to assess common problems and make safe dental management decisions. This new edition contains revised content on Cancer and Women's Health and includes an enhanced ebook plus patient-based practice questions with print purchase. Also, each chapter features informative illustrations and well-organized tables to provide you with in-depth details and overall summaries required for understanding and applying medical concepts in dentistry." --
Patient Evaluation, Risk Assessment, and the Diagnostic Process -- Infective Endocarditis -- Hypertension -- Ischemic Heart Disease -- Cardiac Arrhythmias -- Heart Failure (Congestive Heart Failure) -- Pulmonary Disease -- Smoking and Tobacco Use Cessation -- Sleep Disordered Breathing -- Liver Disease -- Gastrointestinal Diseases -- Chronic Kidney Disease and Dialysis -- Sexually Transmitted Diseases -- Diabetes Mellitus -- Adrenal Insufficiency -- Thyroid Diseases -- Women's Health Issues -- AIDS, HIV Infection, and Related Conditions -- Allergy -- Rheumatologic Disorders -- Organ Transplantation -- Disorders of Red Blood Cells -- Disorders of White Blood Cells -- Acquired Bleeding Disorders -- Congenital Bleeding and Hypercoagulable Disorders -- Cancer and Oral Care of Patients With Cancer -- Neurologic Disorders -- Psychiatric Disorders -- Substance Use Disorders -- Guide to Management of Common Medical Emergencies in the Dental Office -- Guidelines for Infection Control in Dental Health Care Settings -- Therapeutic Management of Common Oral Lesions ∗ -- Drug Interactions of Significance in Dentistry -- Herbal Supplements Used in Complementary and Alternative Medicine of Potential Importance in Dentistry -- Answers to Practice Test Questions.
Includes bibliographical references and index.
Online resource; title from PDF title page (Elsevier, viewed June 26, 2023).
Keywords: Chronically ill -- Dental care; Oral Manifestations; Course 4620 -- DH2 Textbooks